Propuesta de negocio de una estrategia alterna para el manejo de desecho de reencauche (ripio), en la obtención de negro de humo bajo el concepto de economía circular caso de estudio empresa: Reencauchadora Renovando S.A.S ubicada en el municipio Mosquera, Cundinamarca (2021)
The generation of end-of-life tires as waste is a problem present worldwide, in the case of Colombia, actions were taken such as the circular economy strategy where said waste is prioritized for its collection and subsequent treatment. The most widely used method in the handling of tires in the country is retreading, allowing the reduction in the generation of waste, lengthening the useful life of tires, as it is a method aimed at the circular economy, the waste that is not analyzed in depth is not analyzed in depth. They are generated and in turn strategies are not sought to take advantage of them, as is the case of rubble. With the above, it is intended to develop a business proposal as an alternative for the management of retreading waste (gravel) to obtain carbon black framed in the circular economy model, for the retreading company Renovando SAS in the municipality of Mosquera, Cundinamarca. Based on the financial projection and mainly the ecocanvas, it is obtained that, by implementing the business model, the change it generates in the ecological and social aspects is positive; In the first instance, the change to business models that generate circularity in the productive chain of the retreading sector is promoted, in turn, the consumer's perception of the importance of proper handling of end-of-life tires is changed.